Evaluation of exhaust emissions of diesel engine using pyrolysis waste plastics fuel - Sudrajad, Agung; Sunardi, Sunardi; Rosyadi, Imron; Iskandar, Deni (Journal of Mechanical Engineering, Science, and Innovation, 2024)
The increase in the number of vehicles is one of the causes of increasing air pollution. In addition, plastic waste is a type of inorganic waste that has long decomposed, plastic waste can be recycled into fuel oil. But each type of fuel has characteristic properties, this affects the exhaust emissions resulting from the combustion process. The purpose of this study is to determine the exhaust gas emissions (CO, HC, CO2 ) from Single Cylinder R175A type diesel engines with the three kind of fuel such as 100% plastic fuel oil, dexlite, and a mixture of plastic oil fuel and dexlite with a mixture ratio of 30% plastic oil: 70% dexlite (PO30), 50% plastic oil: 50% dexlite (PO50) and 70% plastic oil: 30% dexlite (PO70). The result obtained is that carbon monoxide (CO) exhaust emissions increase with increasing rpm, hydrocarbon (HC) emissions decrease with increasing rpm. The use of plastic fuel oil produces the lowest carbon dioxide (CO2) emissions.